235 Assessing coding of diagnosis for atypical parkinsonian syndromes. Issue 6 (27th May 2022) - Zhong, G; Massey, L; Thomas, S; Ghosh, B
Abstract : Background: Atypical Parkinsonian syndromes, including Progressive Supranuclear Palsy (PSP), Multiple System Atrophy (MSA) and Corticobasal Syndrome (CBS), are rare neurodegenerative diseases. Reports showed that the use of the health services for patients with these diseases is underestimated. The NHS uses International Classification of Disease revision 10 (ICD-10) to code health use which has led to error in patient data for these diseases, as they are relatively new entries to this system and there were changes in coding practice in 2016. Aims: To retrospectively investigate the scale of miscoding of PSP, MSA and CBS in England since the introduction of ICD-10. Methods: Freedom of information requests were issued to 150 NHS trusts in England to investigate their method of coding and determine the coding error rate. Results: The coding error rates prior to, and after 2016 respectively were: 29.5%, 0% (PSP); 3.8%, 2.3% (MSA); 24.2%, 24.2% (CBS). The indexing for CBS is difficult as no specific coding exists for CBS in ICD-10. Conclusion: The high error rate for PSP is contributed by miscoding of PSP (G23.1) as MND (G12.2), due to the coding techniques employed. These errors have largely been rectified in later versions of ICD-10 with the exception of CBS. ggz1g17@soton.ac.uk